2020
DOI: 10.1136/bmjopen-2020-038406
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative investigation of trace-based communication: how are traces conceptualised in healthcare teamwork?

Abstract: ObjectivesThis interview-based qualitative study aims to explore how healthcare providers conceptualise trace-based communication and considers its implications for how teams work. In the biological literature, trace-based communication refers to the non-verbal communication that is achieved by leaving ‘traces’ in the environment and other members sensing them and using them to drive their own behaviour. Trace-based communication is a key component of swam intelligence and has been described as a critical proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Ants, termites and social bees may likewise use chemically complex pheromonal signals that can function to recruit others into mating aggregations, onto profitable food sources or towards new nesting sites [11]. We have demonstrated that healthcare teams regularly use multiple forms of communication, including trace objects and other forms of indirect communication [12]. Ophthalmoscopes, bedside charts, instrument trays, syringes, among other objects are, in a way, like pheromones; they can be used to passively communicate messages to team mates, much like how ants and other social insects can communicate with their nestmates.…”
Section: Learning From Sociobiology -The Key Principlesmentioning
confidence: 96%
“…Ants, termites and social bees may likewise use chemically complex pheromonal signals that can function to recruit others into mating aggregations, onto profitable food sources or towards new nesting sites [11]. We have demonstrated that healthcare teams regularly use multiple forms of communication, including trace objects and other forms of indirect communication [12]. Ophthalmoscopes, bedside charts, instrument trays, syringes, among other objects are, in a way, like pheromones; they can be used to passively communicate messages to team mates, much like how ants and other social insects can communicate with their nestmates.…”
Section: Learning From Sociobiology -The Key Principlesmentioning
confidence: 96%